2021
DOI: 10.1002/term.3197
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of three dimensional bioactive Sr2+substituted apatite scaffolds by gel‐casting technique for hard tissue regeneration

Abstract: This study aimed to fabricate three-dimensional (3D) bioactive Sr 2+ -substituted apatite (Sr-HAP) scaffolds prepared by gel-casting with polymer sponge infiltration technique. 3D Sr-HAP scaffolds were prepared as engineering constructs with interconnected porous structure with a pore size of 200-600 μm ranging from a 10 � 10 � 6 mm size was designed. The characterization of X-ray diffraction, field emission scanning electron microscopy, and energy dispersion spectroscopy was utilized in order to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The number of BMSCs, the expression of osteoblast marker genes, cell migration, and the area of mineralized nodules increased in Sr-CSH/HA. Ramadas et al [ 58 ] prepared a Sr-substituted HA scaffold (Sr-HAP). In vivo tests showed that Sr-HAP successfully healed a 4 mm shin bone defect in rabbits after implantation in 45 days, and histological images showed it improved cell proliferation and new bone formation in the porous scaffold-treated group.…”
Section: Biomaterials Compound With Srmentioning
confidence: 99%
“…The number of BMSCs, the expression of osteoblast marker genes, cell migration, and the area of mineralized nodules increased in Sr-CSH/HA. Ramadas et al [ 58 ] prepared a Sr-substituted HA scaffold (Sr-HAP). In vivo tests showed that Sr-HAP successfully healed a 4 mm shin bone defect in rabbits after implantation in 45 days, and histological images showed it improved cell proliferation and new bone formation in the porous scaffold-treated group.…”
Section: Biomaterials Compound With Srmentioning
confidence: 99%
“…Since CaPO 4 are either thermally unstable (MCPM, MCPA, DCPA, DCPD, OCP, ACP, CDHA) or have a melting point at temperatures exceeding ~1400 • C with a partial decomposition (α-TCP, β-TCP, HA, FA, TTCP), only the first and the second consolidation approaches are used to prepare bulk bioceramics and scaffolds. The methods include uniaxial compaction [154,183,184], isostatic pressing (cold or hot) [87, [185][186][187][188][189][190][191], granulation [192][193][194][195][196][197][198], loose packing [199], slip casting [75,[200][201][202][203][204][205], gel casting [163,[206][207][208][209][210][211], pressure mold forming [212][213][214], injection molding [215][216][217][218], polymer replication [219][220][221][222][223][224]...…”
Section: Forming and Shapingmentioning
confidence: 99%
“…15 The main inorganic component of bone is not a chemically homogeneous substance as it also contains trace amounts of biologically relevant elements such as magnesium (Mg), strontium (Sr), zinc (Zn) and silicon (Si) that are crucial for bone growth, development and repair. 16–19 The incorporation of these elements in bone graft substitute materials is expected to bring biological benefits for the engineered scaffolds. The replacement of calcium (Ca) by magnesium (Mg) in the apatite (HAP) lattice is likely to occur within a narrow molar composition range (up to around 10%).…”
Section: Introductionmentioning
confidence: 99%